MANIFESTASI PENYAKIT PERIODONTAL PADA PENDERITA AIDS - A. Mardiana Suriamiharja; Hasanuddin Thahir (Faculty of Dentistry, Universitas Indonesia, 2015)
Recent articles show that the HIV-AIDS-suffering number tends to increase among people in develop as well as in developing countries. The sufferes mostly lie in the interval of productive ages, i.e. 15 to 49 years old. This trend needs serious action and eager endeavor to handle the lives of sufferers and to safe the remainder as fast as possible. As part of the related action, it is of importance to examine the initial manifestation of the HIV-AIDS on the periodontal tissue in oral cavity. The dentist might monitor the development from its initial stage in order to formulate the therapy. To achieve such capability, the knowledge of this development is urgently required even though at the minimal level. Though the therapy for the HIV-AIDS sufferers are not quite different with other normal periodontal tissues, nevertheless the dentist needs to serve the sufferers satisfying their therapy to increase the spirit of their lives. As a conclusion of this literature study, the dentists are urgently to prepare the comprehension of its clinical diagnostics, diseases development, as well as rationale in modified the therapy suitable for the true condition.